2018
DOI: 10.16965/ijar.2018.306
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of Pedicles of Dried Adult Human Lumbar Vertebrae in Udaipur Zone

Abstract: It has been suggested that reduced inter-pedicular distance is one of the cause of primary narrowing of the spinal canal may lead to low back pain.Transpedicular approaches are being widely used in many surgeries such as bone biopsy, bone grafting, Pedicle screw fixation, vertebroplasty and kyphoplasty. The morphometric data of lumbar vertebra from Udaipur district i.e. in southern Rajasthan is to the best of our knowledge, virtually unexplored so we under took this study.Aims and objectives: The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 3 publications
5
10
0
Order By: Relevance
“…A study revealed that the mean pedicle breadth gradually decreases from L1 to L5 vertebrae 23 which is consistent with the present study. However, a study amongst Saudi Arabian population had found a gradual increasing pattern of pedicle breadth from L1 to L5 in both genders 8 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A study revealed that the mean pedicle breadth gradually decreases from L1 to L5 vertebrae 23 which is consistent with the present study. However, a study amongst Saudi Arabian population had found a gradual increasing pattern of pedicle breadth from L1 to L5 in both genders 8 .…”
Section: Discussionsupporting
confidence: 93%
“…In a study on lumbar vertebrae, the mean pedicle breadth was noticed to have insignificant differences between right and left sides 10 which is consistent with the present study except at L2 and L4. These results are also supported by a study in which the breadth was not found to have significant differences between right and left pedicles 23 which is also consistent with this study. A study also observed that mean pedicle breadth values were found to have significant differences between males and females 8 which is different to this study except at L1.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…low back pain is a musculoskeletal condition affecting the adults (Vinaya Swetha, yuvaraj babu and Mohanraj, 2018). It is one of the main health problems all over the world and around 75% of the population is estimated to have experienced it at least at some point of their life (Choubisa andbabel, 2018) (banik et al, 2019). lumbar spinal stenosis is the common cause in older age group which is narrowing of the spinal canal in which the antero-posterior and lateral measurements of the canal are less than the normal value for the particular age and sex.…”
Section: Introductionmentioning
confidence: 99%